PENGARUH KUALITAS PRODUK, HARGA DAN MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK TAS, JAKET DAN SEPATU EIGER ( STUDI KASUS PADA MAHASISWA KEHUTANAN UNIVERSITAS PAPUA) - Heipon, Samuel Z; Bajari, Makarius; Hayati, ismi (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2024)
This research aims to analyze product quality, price and brand variables on purchasing decisions for Eiger bags, jackets and shoes among students at the Faculty of Forestry, University of Papua. The type of research used is a qualitative approach to associative types of problems. The population in the research were students of the Faculty of Forestry, University of Papua who had used Eiger products in student activities and the sample in the research was 73 respondents using the Slovin method as a sampling method. The data collection method uses primary data, namely observation, interviews and questionnaires and secondary data, namely books, journals, articles and internet sites. This research instrument uses a Likert scale with a data analysis method, namely multiple linear regression analysis. The results of this research show that the independent variable, namely product quality, has no effect on purchasing decisions, but the other two independent variables, price and brand, have a partially significant effect on purchasing decisions and the results of simultaneous testing of the independent variables, namely product quality, price and brand, simultaneously influence purchasing decisions. Eiger bags, jackets and shoes.